A high-load single-atom catalyst and its preparation method and application
By condensing polycondensation in solvent to form a two-dimensional layered support and reacting with metal salt precursors, a single-atom catalyst with high load is prepared, which solves the problems of low load and poor universality of synthesis strategies in the prior art, and achieves high efficiency , low-cost single-atom catalyst preparation, suitable for a variety of transition metals, with excellent catalytic performance and cycle stability.
Patent Information
- Application Number
- CN202310016501.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-01-06
AI Technical Summary
The existing single-atom catalyst has low metal loading, poor universality, high cost and low efficiency, which limits its further development in industrial applications.
The polycondensation reaction of melamine, melamine, L-alanine and phytic acid in the presence of solvents is carried out to form a two-dimensional layered carrier, and the metal salt precursor is added to lyophilize and high-temperature treatment to prepare a high load capacity Single-atom catalyst, support is a carbon material doped with nitrogen-oxygen, suitable for a variety of transition metals.
The maximum loading of a single-atom catalyst is achieved to reach 35 wt%, with good catalytic performance and cycle stability, suitable for homogeneous and heterogeneous catalytic reactions, and the preparation method is low in cost and high efficiency, and is suitable for large-scale production.
Smart Images

Figure CN115990501B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalyst preparation, and in particular relates to a high-load single-atom catalyst and a preparation method and application thereof. Background Art
[0002] Single-atom catalysis bridges the gap between homogeneous catalysis and heterogeneous catalysis, and has become one of the current research hotspots in the field of catalysis. Compared with traditional catalysts, single-atom catalysts have significant advantages, such as theoretically 100% atomic utilization, better activity at unsaturated metal sites, clear structural active sites that are more likely to reveal the catalytic process, and high activity and selectivity, which make them have great prospects for industrial applications.
[0003] However, the challenge in synthesizing single-atom catalysts is that the support cannot effectively stabilize single atoms, because as the particle diameter decreases, the surface free energy increases sharply, and metal atoms tend to aggregate into larger particles. Moreover, as the loading increases, monodispersed atoms are less likely to form. Therefore, many current single-atom catalysts have relatively low metal loadings, generally less than 1wt%, which greatly limits the further application of single-atom catalysts in industry.
[0004] It is worth noting that some emerging synthetic strategies have been proposed to obtain such a unique class of high-loaded single-atom catalysts, such as Gu Meng et al. synthesized 18wt% Ir single atoms on NiO carriers rich in O defects; Hu Jinsong's research group obtained up to 12.1wt% Co single atoms by adsorbing metal precursors on carbon carriers with huge specific surface areas; Li Yadong's research group synthesized ultra-high 30wt% Fe single atoms by polymer pyrolysis. Experimental results show that these synthesized high-loaded single-atom catalysts exhibit excellent performance in fields such as electrocatalysis.
[0005] However, the above-mentioned synthesis strategies all have their own limitations, such as being only applicable to the synthesis of a certain type of single-atom catalyst, poor universality, or complicated preparation steps, low efficiency, and high cost. Therefore, developing a universal, low-cost strategy for synthesizing high-load single-atom catalysts is currently a challenge. Summary of the invention
[0006] The purpose of the present invention is to provide a high-load single-atom catalyst and its preparation method and application. The obtained single-atom catalyst has a unique coordination structure, and its maximum loading can reach 35wt%; and the preparation method of the single-atom catalyst has good universality, is applicable to a variety of transition metals, and has low cost, high efficiency, simple operation, no need for acid etching, good reproducibility, controllable loading, and is more conducive to large-scale production.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a single atom catalyst comprises the following steps:
[0009] S1. In the presence of a solvent, melamine, cyanuric acid, L-alanine and phytic acid undergo polycondensation to obtain a two-dimensional layered carrier, which is referred to as 2D-polymer.
[0010] S2, adding a precursor containing a metal salt to the 2D-polymer and stirring to obtain a metal-containing polymer, which is recorded as M@2D-polymer;
[0011] S3, freeze-drying the M@2D-polyme to obtain M@2D-polyme powder;
[0012] S4. Subjecting the M@2D-polyme powder to high temperature treatment to obtain the single atom catalyst.
[0013] In step S1, the solvent is selected from at least one of deionized water, ethanol and acetone.
[0014] In step S1, the mass volume ratio of the melamine, the cyanuric acid, the L-alanine and the phytic acid is: 1g: (0.5-4)g: (0.5-4)g: (100-500)μL; preferably 1g: (1-2)g: (1-2)g: (200-400)μL.
[0015] In step S1, the conditions of the polycondensation reaction are: temperature of 20-150° C., preferably 60-100° C., and time of 1-1.5 h, preferably 1 h.
[0016] In step S1, when the single atom is Fe, Co, Ni, Cu or Zn, the solvent is deionized water; when the single atom is Ru or Ir, the solvent is ethanol.
[0017] In step S2, the metal salt is selected from at least one of nitrates and hydrochlorides corresponding to the metal element.
[0018] In step S2, the mass ratio of the precursor containing the metal salt to the melamine is (0.001-0.5):1; preferably (0.02-0.25):1.
[0019] In step S2, the stirring makes the reaction system in a muddy state.
[0020] In step S3, the freeze-drying conditions are: under vacuum conditions, the temperature is -5--20°C, preferably -10--15°C, and the time is 1-22h, preferably 20-22h.
[0021] In step S4, the high temperature pyrolysis conditions are: under an inert gas atmosphere, the temperature is 500-800°C, preferably 700-800°C, the heating rate is 2-10°C / min, preferably 2-3°C / min, and the time is 1-3h, preferably 1-2h.
[0022] The present invention also provides a single-atom catalyst obtained by the preparation method.
[0023] The single-atom catalyst comprises the following components: a two-dimensional layered support and a single atom supported on the two-dimensional layered support;
[0024] The two-dimensional layered carrier is a nitrogen-oxygen doped carbon material.
[0025] The single atom is a transition metal element, preferably at least one of Fe, Co, Ni, Cu, Zn, Ru and Ir.
[0026] The structure of the single atom catalyst is M-N3O1 coordination, where M is a single atom.
[0027] The loading amount of the single atom is 0.1%-35%.
[0028] The pore size of the two-dimensional layered carrier is 0.1-100 nm, and the specific surface area is 100-1000 m 2 1g.
[0029] The present invention also provides applications of the single-atom catalyst in oxidation reactions, electrocatalysis, photoelectrocatalysis and hydrogenation catalysis.
[0030] The beneficial effects of the present invention are as follows:
[0031] 1. The series of single-atom catalysts provided by the present invention have a unique coordination structure, and their two-dimensional layered carriers have a high loading capacity of up to 35wt%, so they can exhibit excellent catalytic performance when used in homogeneous and heterogeneous catalytic reactions.
[0032] 2. The copper single-atom catalyst provided by the present invention also has good cycle stability.
[0033] 3. The preparation method provided by the present invention can quickly prepare single atoms with high loading in large quantities, is applicable to a series of transition metal elements, and has better universality.
[0034] 4. The precursor used in the preparation method provided by the present invention is cheap and easily available, with low cost, and the preparation process is simple and efficient, and a certain scale production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1This is a spherical aberration corrected high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) photograph of the copper single atom catalyst prepared in Example 1 of the present invention.
[0036] Figure 2 This is a surface scanning distribution diagram of the copper single atom catalyst prepared in Example 1 of the present invention.
[0037] Figure 3 This is the K-edge EXAFS Fourier transform spectrum of Cu of the copper single-atom catalyst prepared in Example 1 of the present invention.
[0038] Figure 4 The catalytic performance of the high-load copper single-atom catalyst prepared in Example 1 of the present invention in the oxidation of benzene with hydrogen peroxide.
[0039] Figure 5 The stability of the high-load copper single-atom catalyst prepared in Example 1 of the present invention in the oxidation reaction of benzene with hydrogen peroxide. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0041] The experimental methods in the following examples, unless otherwise specified, are conventional methods and are performed according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0042] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0043] Example 1. Preparation of High-Loaded Cu Single Atom Catalyst
[0044] The specific preparation steps are as follows:
[0045] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 400 μL of phytic acid were added to deionized water as solvent, and in situ polycondensed at 100 °C for 1 h to obtain a 2D-polymer;
[0046] (2) Add 270 mg Cu(NO3)2·4H2O and stir until it becomes a slurry to obtain a 2D-polymer containing Cu;
[0047] (3) placing the obtained 2D-polymer containing Cu in a vacuum dryer and freeze-drying it at -10°C for 22 h to remove the solvent and obtain Cu@2D-polymer powder;
[0048] (4) Under argon protection, the Cu@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-loaded Cu single-atom catalyst with a loading of 22 wt%.
[0049] The spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of the obtained copper single-atom catalyst is shown in Figure 2. Figure 1 As shown, it proves that copper exists in single atomic form.
[0050] The surface scanning distribution diagram of the obtained copper single atom catalyst is as follows: Figure 2 As shown, it is proved that the copper element is evenly distributed in the catalyst material. The pore size of the two-dimensional layered carrier is 3nm and the specific surface area is 350m 2 1g.
[0051] The obtained Cu K-edge EXAFS Fourier transform spectrum of the copper single atom catalyst is as follows: Figure 3 As shown, it is proved that copper has a Cu-N3O1 coordination structure.
[0052] Example 2: Preparation of High-Loaded Fe Single Atom Catalyst
[0053] The specific preparation steps are as follows:
[0054] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 400 μL of phytic acid were added to deionized water and in situ polycondensed at 100 °C for 1 h to obtain a 2D-polymer;
[0055] (2) Add 350 mg of Fe(NO3)2·9H2O and stir until it becomes a slurry to obtain a 2D-polymer containing Fe;
[0056] (3) placing the Fe-containing 2D-polymer in a vacuum dryer and freeze-drying it at -10°C for 22 h to remove the solvent and obtain Fe@2D-polymer powder;
[0057] (4) Under argon protection, the Fe@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-loaded Fe single-atom catalyst with a loading of 21 wt%.
[0058] Example 3. Preparation of High-Loaded Co Single Atom Catalyst
[0059] The specific preparation steps are as follows:
[0060] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 400 μL of phytic acid were added to deionized water and in situ polycondensed at 100 °C for 1 h to obtain a 2D-polymer;
[0061] (2) Add 280 mg Co(NO3)2·6H2O and stir until it becomes a slurry to obtain a 2D-polymer containing Co;
[0062] (3) placing the Co-containing 2D-polymer in a vacuum dryer and freeze-drying it at -10 °C for 22 h to remove the solvent and obtain Co@2D-polymer powder;
[0063] (4) Under argon protection, the Co@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-loaded Co single-atom catalyst with a loading of 21 wt%.
[0064] Example 4. Preparation of High-Loaded Ni Single Atom Catalyst
[0065] The specific preparation steps are as follows:
[0066] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 200 μL of phytic acid were added to deionized water and in situ polycondensed at 100 °C for 1 h to obtain a 2D-polymer;
[0067] (2) Add 260 mg Ni(NO3)2·6H2O and stir until it becomes a slurry to obtain a 2D-polymer containing Ni;
[0068] (3) placing the Ni-containing 2D-polymer in a vacuum dryer and freeze-drying it at -10 °C for 22 h to remove the solvent and obtain Ni@2D-polymer powder;
[0069] (4) Under argon protection, the Ni@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-loaded Ni single-atom catalyst with a loading of 18 wt%.
[0070] Example 5. Preparation of high-load Zn single-atom catalyst
[0071] The specific preparation steps are as follows:
[0072] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 200 μL of phytic acid were added to deionized water and in situ polycondensed at 100 °C for 1 h to obtain a 2D-polymer;
[0073] (2) Add 450 mg Zn(NO3)2·6H2O and stir until it becomes a slurry to obtain a 2D-polymer containing Zn;
[0074] (3) placing the Zn-containing 2D-polymer in a vacuum dryer and freeze-drying it at -10 °C for 22 h to remove the solvent and obtain Zn@2D-polymer powder;
[0075] (4) Under argon protection, the Zn@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-load Zn single-atom catalyst with a loading of 35 wt%.
[0076] Example 6: Preparation of high-load Ru single-atom catalyst
[0077] The specific preparation steps are as follows:
[0078] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 400 μL of phytic acid were added to ethanol and subjected to in-situ polycondensation at 60 °C for 1 h to obtain a 2D-polymer;
[0079] (2) Add 90 mg of RuCl3 and stir until it becomes a slurry to obtain a 2D-polymer containing Ru;
[0080] (3) placing the Ru-containing 2D-polymer in a vacuum dryer and freeze-drying it at -10°C for 22 h to remove the solvent and obtain Ru@2D-polymer powder;
[0081] (4) Under argon protection, the Ru@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-loaded Ru single-atom catalyst with a loading of 17 wt%.
[0082] Example 7. Preparation of High-Loaded Ir Single Atom Catalyst
[0083] The specific preparation steps are as follows:
[0084] (1) 2 g of melamine, 2 g of cyanuric acid, 2 g of L-alanine and 400 μL of phytic acid were added to ethanol and subjected to in-situ polycondensation at 60 °C for 1 h to obtain a 2D-polymer;
[0085] (2) Add 50 mg of IrCl3 and stir until it becomes a slurry to obtain a 2D-polymer containing Ir;
[0086] (3) placing the 2D-polymer containing Ir in a vacuum dryer and freeze-drying it at -10 °C for 22 h to remove the solvent and obtain Ir@2D-polymer powder;
[0087] (4) Under argon protection, the Ir@2D-polymer powder was heated to 700°C at a rate of 2°C / min, maintained for 2 h, and then cooled naturally to obtain a high-loaded Ir single-atom catalyst with a loading of 14 wt%.
[0088] It can be seen from Examples 1-7 that the nitrogen-oxygen-doped two-dimensional layered carrier 2D-polymer prepared by the in-situ polycondensation reaction of melamine, cyanuric acid, L-alanine and phytic acid can form a unique coordination structure with a variety of single atoms (Fe, Co, Ni, Cu, Zn, Ru and Ir), and thus has good universality; at the same time, through this coordination structure, the loading amount of single atoms can be significantly increased, up to 35%, thereby making the prepared catalyst have better catalytic performance; in addition, the raw materials prepared in this method are cheap and easily available, the preparation process is simple and efficient, and the loading amount is controllable.
[0089] Application Example 1
[0090] Taking the Cu single-atom catalyst prepared in Example 1 as an example, the reaction of directly oxidizing benzene to prepare phenol by hydrogen peroxide in one step is as follows:
[0091] In a 25mL sealed glass reactor, 10mg of the Cu single atom catalyst prepared in Example 1, 0.3mL of benzene, 0.4mL of H2O2 (30%) (the molar ratio of benzene to H2O2 is 1:1), and 3.0mL of acetonitrile were added to start the reaction at a temperature of 60°C. After the reaction was completed, the reaction product was filtered with a filter membrane and ethyl acetate was added to extract the catalytic product.
[0092] The catalytic product was analyzed by gas chromatography (GC, Shimadzu, GC2010plus) and gas mass spectrometry (GCMS, Shimadzu, GCMS-QP2010S) with n-tridecane as the internal standard.
[0093] The results are as follows:
[0094] The performance of Cu single-atom catalysts in the oxidation of benzene with hydrogen peroxide, such as Figure 4As shown, after 24 hours of reaction, the conversion rate of benzene is 22%, the oxidation selectivity of benzene is 100%, and the corresponding utilization rate of hydrogen peroxide is 22%; after 144 hours of reaction, the conversion rate of benzene is 50.1%, the oxidation selectivity of benzene is 99.5%, and the corresponding utilization rate of hydrogen peroxide is 50.1%; it can be concluded that in the reaction of directly oxidizing benzene to prepare phenol by hydrogen peroxide one-step method, the use of the high-load copper single-atom catalyst provided by the present invention can significantly improve the oxidation selectivity of benzene and the utilization rate of hydrogen peroxide.
[0095] Application Example 2
[0096] The specific steps of preparing phenol with a recycled catalyst are as follows:
[0097] (1) Catalyst regeneration:
[0098] The reaction solution after 24 hours of reaction in Application Example 1 was separated, washed three times with ethyl acetate, and vacuum dried at 60° C. for 2 hours to obtain a regenerated Cu single atom catalyst;
[0099] (2) In a 25 mL sealed glass reactor, 10 mg of the regenerated Cu single atom catalyst, 0.3 mL of benzene, 0.4 mL of H2O2 (30%) (the molar ratio of benzene to H2O2 is 1:1), and 3.0 mL of acetonitrile were added to start the reaction at a temperature of 60°C for 24 h. After the reaction was completed, the reaction product was filtered with a filter membrane and ethyl acetate was added to extract the catalytic product.
[0100] (3) The obtained reaction solution was separated again, washed with ethyl acetate three times, and vacuum dried at 60° C. for 2 h to obtain a regenerated Cu single atom catalyst, which was recycled 10 times.
[0101] The catalytic products obtained each time were analyzed by gas chromatography (GC, Shimadzu, GC2010plus) and gas mass spectrometry (GCMS, Shimadzu, GCMS-QP2010S) with n-tridecane as the internal standard.
[0102] The stability of the recycled copper single atom catalyst in the oxidation of benzene with hydrogen peroxide, such as Figure 5 As shown, under the condition that the molar ratio of benzene to H2O2 is 1:1, the conversion rate of benzene is maintained at about 21%, the oxidation selectivity of benzene is maintained at about 99.7, and the corresponding utilization rate of hydrogen peroxide is maintained at about 21%. This proves that the high-load copper single-atom catalyst provided by the present invention can be recycled more than 10 times and has good recycling performance.
[0103] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a single atom catalyst, comprising the following steps: S1. In the presence of a solvent, melamine, cyanuric acid, L-alanine and phytic acid undergo polycondensation to obtain a two-dimensional layered carrier, which is referred to as 2D-polymer. S2, adding a precursor containing a metal salt to the 2D-polymer and stirring to obtain a metal-containing polymer, which is recorded as M@2D-polymer; S3, freeze-drying the M@2D-polymer to obtain M@2D-polymer powder; S4. Subjecting the M@2D-polymer powder to high temperature treatment to obtain the single atom catalyst.
2. The method for preparing a single atom catalyst according to claim 1, characterized in that: In step S1, the solvent is selected from at least one of deionized water, ethanol and acetone; The mass volume ratio of the melamine, the cyanuric acid, the L-alanine and the phytic acid is: 1 g: (0.5-4) g: (0.5-4) g: (100-500) μL; The conditions of the polycondensation reaction are: temperature of 20-150° C. and time of 1-1.5 h.
3. The method for preparing a single atom catalyst according to claim 1 or 2, characterized in that: In step S1, when the single atom is Fe, Co, Ni, Cu or Zn, the solvent is deionized water; When the single atom is Ru or Ir, the solvent is ethanol.
4. The method for preparing a single atom catalyst according to claim 1 or 2, characterized in that: In step S2, the metal salt is selected from at least one of a nitrate and a hydrochloride of a corresponding metal element; The mass ratio of the precursor containing the metal salt to the melamine is (0.001-0.5): 1; The stirring makes the reaction system sludge-like.
5. The method for preparing a single atom catalyst according to claim 1 or 2, characterized in that: In step S3, the freeze-drying conditions are: under vacuum conditions, temperature is -5 to -20°C, and time is 1-22 hours.
6. The method for preparing a single atom catalyst according to claim 1 or 2, characterized in that: In step S4, the high temperature pyrolysis conditions are: under an inert gas atmosphere, a temperature of 500-800° C., a heating rate of 2-10° C. / min, and a time of 1-3 h.
7. The single atom catalyst obtained by the preparation method according to any one of claims 1 to 6.
8. The single atom catalyst according to claim 7, characterized in that: The invention comprises the following components: a two-dimensional layered carrier and a single atom loaded on the two-dimensional layered carrier; The two-dimensional layered carrier is a nitrogen-oxygen doped carbon material; The single atom is Fe, Co, Ni, Cu, Zn, Ru or Ir; The structure of the single atom catalyst is M-N3O1 coordination, where M is a single atom.
9. The single atom catalyst according to claim 8, characterized in that: The loading amount of the single atom is 14 wt %-35 wt %; The pore size of the two-dimensional layered carrier is 0.1-100 nm, and the specific surface area is 100-1000 m 2 / g.
10. Use of the single-atom catalyst according to any one of claims 7 to 9 in the fields of oxidation reaction, electrocatalysis, photoelectrocatalysis or hydrogenation catalysis.
